Proceedings of the First Joint WOSP/SIPEW International Conference on Performance Engineering 2010
DOI: 10.1145/1712605.1712613
|View full text |Cite
|
Sign up to set email alerts
|

State dependence in performance evaluation of component-based software systems

Abstract: Integrating rising variability of software systems in performance prediction models is crucial to allow widespread industrial use of performance prediction. One of such variabilities is the dependency of system performance on the context and history-dependent internal state of the system (or its components). The questions that rise for current prediction models are (i) how to include the state properties in a prediction model, and (ii) how to balance the expressiveness and complexity of created models.Only a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Several component-based prediction approaches, e.g. Palladio [23,30,6], CB-SPE [7], ROBOCOP [8] (see also a survey in [5]) derive the benefits of reusing well-documented component specifications. In our approach we focus on the questions of resourceawareness and adaptivity of systems as well as on the readability aspects of the formalism.…”
Section: Proposed Visualisation Approachmentioning
confidence: 99%
“…Several component-based prediction approaches, e.g. Palladio [23,30,6], CB-SPE [7], ROBOCOP [8] (see also a survey in [5]) derive the benefits of reusing well-documented component specifications. In our approach we focus on the questions of resourceawareness and adaptivity of systems as well as on the readability aspects of the formalism.…”
Section: Proposed Visualisation Approachmentioning
confidence: 99%
“…Several component-based prediction approaches, e.g. Palladio [8], CB-SPE [9], ROBO-COP [10] derive the benefits of reusing well-documented component specifications (cf. also a survey in [11]).…”
Section: Related Workmentioning
confidence: 99%
“…As a proof of the concept, we extended an existing performance prediction framework and employed it in a realworld case study, demonstrating the effect of state modelling on software performance. The paper is an extension of our previous work [16] with an expanded state-effect analysis, an extensive experimental evaluation of newly derived heuristics, and an additional case study.…”
Section: The Contribution Of the Papermentioning
confidence: 99%
“…Along the scope dimension, it distinguishes component-, system-and user-specific states, all defined below. With respect to the time dimension, we examined all the stages of componentbased system life cycle [16], and observed that a state is by nature a dynamic information that evolves independently for individual elements in the system. If it is fixed along life cycle, it is not set before the element gains its identity (instantiation stage in case of a component, assembly stage in case of a system).…”
Section: State Categories In Component-based Systemsmentioning
confidence: 99%